Meningkatan Hasil Belajar Servis Backhand Dalam Permainan Tenis Meja Melalui Model Pembelajaran Kooperatif Tipe Jigsaw Pada Siswa Kelas VII Sekolah Menengah Pertama Negeri I Leksula - Lesnussa, Jeck Adefrid; Solissa, Jonas; Hukubun, Mariana D (MANGGUREBE: Journal Physical Education, Health and Recreation, 2022)
Classroom action research that aims to improve the learning outcomes of table tennis game backhand serve through jigsaw type cooperative learning model for seventh grade students of SMP Negeri 1 Leksula. The population of this study were all seventh grade students of SMP Negeri 1 Leksula totalling 117 people and as many as five classes, each class numbered 23-24 people. The subjects of this study were VII grade students of SMP Negeri I Leksula totalling 25 students with learning instruments used in this study, namely treatment instruments, namely by using learning devices (RPP) and measurement instruments, namely by using rubrics for assessing knowledge, attitudes, and skills. The analysis technique used is descriptive analysis technique. There was an increase from cycle I to cycle II and students had reached the minimum performance criteria, so the research was declared over. Thus the jigsaw type cooperative learning model can be used in learning table tennis games.